2009
DOI: 10.1016/j.scr.2008.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterning of human embryonic stem cells dissects the mesoderm and endoderm lineages

Abstract: Human pluripotent cells such as human embryonic stem cells (hESC) are a great potential source of cells for cell-based therapies; however, directing their differentiation into the desired cell types with high purity remains a challenge. The stem cell microenvironment plays a vital role in directing hESC fate and we have previously shown that manipulation of colony size in a serum- and cytokine-free environment controls self-renewal and differentiation toward the extraembryonic endoderm lineage. Here we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 29 publications
0
76
0
Order By: Relevance
“…However, simulations limited to bulk concentration effects cannot capture differences in local concentration created by underlying cellular activities. For example, the level of endogenous signaling in ESCs is influenced by local cell density, as shown by controlling cell colony size using micropatterning (4,17,18). We have advanced these previous studies by creating a model and cell culture system to demonstrate that a small set of probabilistic rules for individual ligands can give rise to colony-level cellular responses.…”
Section: Discussionmentioning
confidence: 96%
“…However, simulations limited to bulk concentration effects cannot capture differences in local concentration created by underlying cellular activities. For example, the level of endogenous signaling in ESCs is influenced by local cell density, as shown by controlling cell colony size using micropatterning (4,17,18). We have advanced these previous studies by creating a model and cell culture system to demonstrate that a small set of probabilistic rules for individual ligands can give rise to colony-level cellular responses.…”
Section: Discussionmentioning
confidence: 96%
“…It has also been shown that manipulating colony size by micropatterning can direct the cells into mesoderm versus endoderm upon differentiation (Lee et al, 2009), which is likely to be a consequence of edge sensing and a reaction-diffusion mechanism. Micropatterning has also been used to study developmental processes beyond gastrulation, namely during the formation and subsequent characterization of cardiomyocytes .…”
Section: Generating Micropatterns: the Role Of Confining External Sigmentioning
confidence: 99%
“…In one approach micro-contact printing is used to pattern ECM onto tissue culture substrates, thereby specifying hESC colony size and geometry (Peerani, Rao et al 2007; Lee, Peerani et al 2009). …”
Section: Pluripotent Stem Cells Hesc Maintenancementioning
confidence: 99%